Tourette Syndrome and Learning Disabilities: a focus on correlations in a neurodevelopmental perspective - Brambilla Emma (Neuropsychological Trends, 2016)
People with Tourette Syndrome (TS) frequently show the presence of Learning Disabilities (LD) at school age. Literature investigating the correlation between TS and LD is limited: studies focus on the incidence of this correlation, the impact on school achievement and the number of fields affected by these difficulties, show neuropsychological diseases in comorbility and reveal a discrepancy between IQ scores and school results. The most important evidence shows that in some children the appearance of LD and tics coincide. In a neurodevelopmental approach, the origin of both symptoms, TS and LD, can be explained observing the nervous system’s maturation process, through specific steps, which lead to the acquisition of visual, aural and tactile competence, and allow the development of mobility, language and manual ability. As they all develop along a continuum, neurodevelopmental levels that have not been completed always imply neuro-functional anomalies, which can be observed with brain-imaging techniques. Investigating this correlation in a neuropsychological perspective would be useful not only to better understand the underlying functional aspects, but also to properly plan good rehabilitation strategies to apply in everyday clinical practice.